ExpFinder: A hybrid model for expert finding from text-based expertise data. (January 2023) - Kang, Yong-Bin; Du, Hung; Forkan, Abdur Rahim Mohammad; Jayaraman, Prem Prakash; Aryani, Amir; Sellis, Timos
Abstract: Finding an expert plays a crucial role in driving successful collaborations and speeding up high-quality research development and innovations. However, the rapid growth of scientific publications and digital data makes identifying the right experts a challenging problem. Existing approaches for finding experts given a topic can be categorised into information retrieval techniques such as vector space models, document language models, and graph-based models. In this paper, we propose ExpFinder, a new hybrid model for expert finding, that integrates a novel N -gram vector space model, denoted as n VSM, and a graph-based model, denoted as μ CO-HITS, that is a proposed variation of the CO-HITS algorithm. The key of n VSM is to exploit recent inverse document frequency weighting method for N -gram words, and ExpFinder incorporates n VSM into μ CO-HITS to achieve expert finding. We comprehensively evaluate ExpFinder on four different datasets from the academic domains in comparison with six different expert finding models. The evaluation results show that ExpFinder is an highly effective model for expert finding, substantially outperforming all the compared models in 19% to 160.2%. Highlights: We propose a hybrid model, ExpFinder, for expert finding from expertise text data. ExpFinder integrates a novel n-gram vector space model and an extension of CO-HITS. ExpFinder achieves a very high performance over 6 competitive models on 4 datasets.